A new meta-coupling framework to diagnose the inequity hidden in China's cultivated land use. Issue 124 (October 2021) - Chuai, Xiaowei; Gao, Runyi; Li, Jianbao; Guo, Xiaomin; Lu, Qinli; Zhang, Mei; Zhang, Xueru; Liu, Yan
Highlights: A new meta-coupling framework was designed. Cultivated land suppliers were always concentrated in less developed regions. Fully agriculturally efficient regions were always concentrated in less developed regions. Developed regions had greater beneficiaries in interregional trade. Abstract: Agricultural produce consumes various resources and impacts the environment significantly. Domestic trade affects China's regional cultivated land use and its associated agricultural inputs and outputs, causing great inequity among regions through indirect cultivated land use. This study designed a new meta-coupling framework to diagnose inequity in China's cultivated land use. Intra-coupling analysis shows that agricultural elements had a close and positive connection with one another, and cultivated land use plays a key role in determining other inputs and outputs. In the tele-coupling process, cultivated land suppliers were always concentrated in less developed regions. Receivers were mainly located in developed regions. Similar regularity is also obvious in examining flowing characteristics of other land's inputs and outputs. Eastern China showed a relatively extensive amount of cultivated land input and output, while dispersive distribution in middle and western China, especially in terms of the high densities water use in the west. The regional comprehensive intra-coupling effect shows that fully agriculturally efficient regions were always concentrated in undeveloped or less developed regions, which mainly existed in middle and northern China. The regional comprehensive tele-coupling effect also revealed regional inequity. This study considers developed regions greater beneficiaries in interregional trade when analysing economic profit, resource consumption, and environmental damage. In undeveloped regions, these elements have a more profound and lasting negative influence. Thus, enhancing resource utilization efficiency and regional responsibilities should be reconsidered.